Novel polyamide based materials for oil based drilling fluids - Tauanov, Z.; Baptayev, B. (Nazarbayev University, 2013)
Overall, so far 10 amidoamines were synthesized and 6 polyamide emulsifiers were prepared. The next steps are to increase the number of polyamide emulsifiers, testing them for thermal stability and polyemulsion stability, and in drilling fluid condition.
Keywords: first research week; polyamide